Genetic variation in DNMT3B and increased global DNA methylation is associated with suicide attempts in psychiatric patients. (26th October 2012) - Murphy, T. M.; Mullins, N.; Ryan, M.; Foster, T.; Kelly, C.; McClelland, R.; O'Grady, J.; Corcoran, E.; Brady, J.; Reilly, M.; Jeffers, A.; Brown, K.; et al.
<x xml:space="preserve">Abstract</x> Recently, a significant epigenetic component in the pathology of suicide has been realized. Here we investigate candidate functional SNPs in epigenetic‐regulatory genes, DNMT1 and DNMT3B, for association with suicide attempt (SA) among patients with co‐existing psychiatric illness. In addition, global DNA methylation levels [5‐methyl cytosine (5‐mC%)] between SA and psychiatric controls were quantified using the Methylflash Methylated DNA Quantification Kit. DNA was obtained from blood of 79 suicide attempters and 80 non‐attempters, assessed for DSM‐IV Axis I disorders. Functional SNPs were selected for each gene (DNMT1; n = 7, DNMT3B; n = 10), and genotyped. A SNP (rs2424932) residing in the 3′ UTR of the DNMT3B gene was associated with SA compared with a non‐attempter control group (P = 0.001; Chi‐squared test, Bonferroni adjusted P value = 0.02). Moreover, haplotype analysis identified a DNMT3B haplotype which differed between cases and controls, however this association did not hold after Bonferroni correction (P = 0.01, Bonferroni adjusted P value = 0.56). Global methylation analysis showed that psychiatric patients with a history of SA had significantly higher levels of global DNA methylation compared with controls (P = 0.018, Student's t‐test). In conclusion, this is the first report investigating polymorphisms in DNMT genes and global DNA methylation quantification in SA risk. Preliminary findings suggest that allelic variability in DNMT3B may be relevant to the underlying diathesis for suicidal acts and our findings support the hypothesis that aberrant DNA methylation profiles may contribute to the biology of suicidal acts. Thus, analysis of global DNA hypermethylation in blood may represent a biomarker for increased SA risk in psychiatric patients.